Jamee's Noble Dance Devotion at SDN 1 Bireun - Utami, Intan Rizki Junita Tri (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
Peumulia Jamee's dance service activity at SDN 1 Bireun was carried out to introduce traditional Acehnese arts to elementary school students as well as instill character values through cultural arts. The program uses a participatory approach and qualitative methods by involving students in grades V and VI, accompanying teachers, and principals as partners. The implementation of activities includes the preparation stage of dance materials, routine exercises twice a week, performance simulations, and final evaluation. Data were obtained through observation, interviews, documentation, and pre- and post-implementation questionnaires. The results of the service showed a significant improvement in students' dance skills, an understanding of Peumulia Jamee's philosophical values, and confidence in displaying traditional arts in public. Students also show positive behavioral changes in school that reflect the internalization of cultural values. Factors supporting the success of this program include student enthusiasm, teacher and parent support, and adaptation of training methods. This program proves that traditional arts can be an effective means for cultural preservation, character education, and the strengthening of local identity at the elementary school level.